The Future of Nature Conservation in Amazonia: Evidence From Transboundary Protected Areas - Cardona, Walter Cano; de Jong, Wil; Pokorny, Benno (Frontiers in Forests and Global Change, 2022)
Protected areas are a central instrument to implement the Convention on Biological Diversity (CBD), its Strategic Plan for Biodiversity 2011–2020, and the 20 Aichi Biodiversity Targets. Amazonian countries hold 390 million hectares of such protected areas. Aichi Targets 11, 17, and 18 call for their effective governance and management, and the active participation of indigenous and other local resource user groups and respect for traditional knowledge and customary practices. The paper analyzes five transboundary protected areas in Brazil, Peru, and Bolivia to assess to what extent and in which way these objectives achieved. The analysis relies on data and information derived from documentation produced by the IAPA project which aimed to strengthening Amazonian protected area governance and management, and from personal experiences during project implementation. Important progress has been made in local participation and the sharing of economic benefits in protected area governance in the Amazon basin. But power imbalances, lack of legitimacy of decision-makers, unclear responsibilities, unresolved logistical challenges, and the lack of financial support remain major challenges. The functionality of local governance structures, furthermore, is severely threatened by the vagaries of national policies that often put biodiversity conservation and economic development at loggerheads. To ensure the functionality of protected areas in the Amazon region, binding and sufficient commitments by national governments are needed for genuine and effective local governance.